2009
DOI: 10.1016/j.jmva.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of generalized confidence intervals

Abstract: a b s t r a c tGeneralized confidence intervals provide confidence intervals for complicated parametric functions in many common practical problems. They do not have exact frequentist coverage in general, but often provide coverage close to the nominal value and have the correct asymptotic coverage. However, in many applications generalized confidence intervals do not have satisfactory finite sample performance. We derive expansions of coverage probabilities of one-sided generalized confidence intervals and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Unlike the traditional test of average bioequivalence, the explicit equivalence limit (EL) is not available for every endpoint measured in a field study (Hothorn and Oberdoerfer, 2006). Furthermore, varieties of non‐GM conventional crops possess a considerable amount of natural variation (Reynolds et al, 2005; van der Voet et al, 2011) and a single non‐GM variety would not suffice to serve as the reference. Recently, the GMO panel of EFSA mandated each field site to include an assortment of commercial non‐GM reference varieties with a proven history of safe consumption (EFSA, 2010).…”
mentioning
confidence: 99%
“…Unlike the traditional test of average bioequivalence, the explicit equivalence limit (EL) is not available for every endpoint measured in a field study (Hothorn and Oberdoerfer, 2006). Furthermore, varieties of non‐GM conventional crops possess a considerable amount of natural variation (Reynolds et al, 2005; van der Voet et al, 2011) and a single non‐GM variety would not suffice to serve as the reference. Recently, the GMO panel of EFSA mandated each field site to include an assortment of commercial non‐GM reference varieties with a proven history of safe consumption (EFSA, 2010).…”
mentioning
confidence: 99%
“…Although it can be seen that the simulated coverage probabilities are satisfactory according to the above simulation results, we think that the application of the method proposed by Roy and Bose (2009) in this problem can improve the accuracy further, and this will be one topic of our future research.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Almost at the same time, Li et al (2007) and Xu and Li (2006) also found this connection and gave another general method to construct generalized pivotal quantity. Roy and Bose (2009) provided theoretical explanation of the observed empirical behavior of the generalized intervals and suggested several ways to improve the finite sample performance of the generalized intervals.…”
Section: A Brief Review Of Generalized Fiducial Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Asymptotic properties of the CI based on the GPQs have been discussed by Hanning et al . and Roy and Bose . The present article exploits this technique for interval estimation of R , when X 1 and X 2 are independently distributed members of the exponentiated scale family, also known as resilience or frailty parameter family (Marshall and Olkin): G()xλ,0.3emα=Fα()xλ1emResilience family1emor trueG¯()xλ,0.3emα=trueF¯α()xλ,1em1emx0.3em0.3emε0.3em0.3emnormalR,0.3emλ,0.3em0.3emα>01emFrailty family, where λ and α are the scale and resilience (frailty) parameters, respectively and F (.)…”
Section: Introductionmentioning
confidence: 99%